Systematic Review: Where is Current Research on Conversational Analysis? - Lauren, Cendy; Derin, Tatum (Elsya : Journal of English Language Studies, 2020)
As social media and other new communication technologies are integrated into teaching and learning environments, educators and researchers continue to be interested in the discussion that takes place in such spaces. This paper reports the findings and the research gaps grounded from current research articles on conversation analysis (CA). The data is collected from international and highly reputable journal publishers, namely Science Direct, Elsevier, Sage, and Wiley. From the resulting 49 articles collected, the screening excluded 24 articles. Therefore, it is the remaining 25 articles that are systematically reviewed. The results indicate several themes throughout the current research field, i.e. digital CA, theory and methodology construction, body language or nonverbal conversation, atypical interaction, usage of specific phrases, and novel settings and objects. The practical implication of this systematic review is a collection of research gaps and recommendations that researchers can take note of and tackle in future studies.